Environmental Factors and Students’ Learning Approaches: A Survey on Malaysian Polytechnics Students - Ramlee Mustapha; Seri Bunian Mokhtar; Saemah Rahman; Mohd Yusof Husain; Rahayu Ahamad Bahtiar (Intelektual Pustaka Media Utama, 2014)
Several studies have shown the impact of environmental factors on student learning approaches. Despite the importance of such studies, studies on technical learners are few. Thus, this study aimed to determine the influence of learning environment on Polytechnics students’ learning approaches in Malaysia. Learning environment plays an important role in the cognitive, effective and social domains of students because it could improve students’ learning outcomes. Learning approaches refer to the ways students deal with academic tasks that are related to learning outcomes. This study used Course Experience Questionnaire (CEQ) and Revised Two-Factor Study Process Questionnaire (RSPQ-2F) to collect the research data. Data were analyzed using AMOS Version 18. Multiple regressions were conducted to predict learning environment factors that influenced the level of students’ learning approaches. The result shows that effective teaching is a major factor that influences students' deep approach followed by the assessment, learning resources and clear objectives.